Photobiomodulation improves depression symptoms: a systematic review and meta-analysis of randomized controlled trials - Ji, Qipei; Yan, Shichang; Ding, Jilin; Zeng, Xin; Liu, Zhixiang; Zhou, Tianqi; Wu, Zhuorao; Wei, Wei; Li, Huaqiang; Liu, Shuangyue; Ai, Shuangchun (Frontiers in Psychiatry, 2024)
Background: Depression is a common mental illness that is widely recognized by its lack of pleasure, fatigue, low mood, and, in severe cases, even suicidal tendencies. Photobiomodulation (PBM) is a non-invasive neuromodulation technique that could treat patients with mood disorders such as depression.A systematic search of ten databases, including randomized controlled trials (RCTs) for depression, was conducted from the time of library construction to September 25, 2023. The primary outcome was depression. The secondary outcome was sleep. Meta-analysis was performed using RevMan (version 5.4) and Stata (version 14.0). Subgroup analyses were performed to identify sources of heterogeneity. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE).Result: 3,265 studies were retrieved from the database and screened for inclusion in eleven trials. The forest plot results demonstrated that PBM alleviated depression (SMD = -0.55, 95% CI [-0.75, -0.35], I 2 = 46%). But it is not statistically significant for patients' sleep outcomes (SMD = -0.82, 95% CI [-2.41, 0.77], I 2 = 0%, P > 0.05). Subgroup analysis showed that s-PBM was superior to t-PBM in relieving symptoms of depression. The best improvement for t-PBM was achieved using a wavelength This is a provisional file, not the final typeset article of 823 nm, fluence of 10-100 J/cm 2 , irradiance of 50-100 mW/cm 2 , irradiance time of 30 min, treatment frequency < 3/week, and number of treatments > 15 times. The best improvement for s-PBM was achieved using a wavelength of 808 nm, fluence ≤ 1J/cm 2 , irradiance of 50-100 mW/cm 2 , irradiance time ≤ 5 min, treatment frequency ≥ 3/week, number of treatments > 15 times. All results had evidence quality that was either moderate or very low, and there was no bias in publication.We conclude that PBM is effective in reducing depression symptoms in patients. However, the current number of studies is small, and further studies are needed to extend the current analysis results.